INVESTIGATING THE SIGNIFICANCE OF INSTITUTIONAL CONTEXTS IN DETERMINING FINANCIAL PERFORMANCE: A STUDY OF BERJAYA LAND BERHAD - Yang Yi Fan; Ooi Kok Loang (Journal of Islamic, Social, Economics and Development, 2023)
This article investigates the relationship between organizational characteristics and the financial performance of service businesses, utilizing variables such as liquidity, leverage, asset utilization, market share, and firm size. To gauge the impact of these factors, we use return on assets (ROA) and return on equity (ROE) ratios. The study finds that the profitability of service providers is a good indicator of the quality of management employed by the company. While productivity in service businesses has historically lagged behind property firms, we examine whether service providers can also adopt the management strategies and organizational elements that have contributed to the financial success of property firms. To this end, we examine the bottom line of the company as an indicator of management success. Our research methodology has potential applications in the business world, as the findings can assist managers in better comprehending the nature of various organizational components, leading to improved decision-making. Overall, this study contributes to a deeper understanding of the connection between organizational characteristics and financial performance in service businesses.